PELATIHAN ANALISIS KORELASI DAN REGRESI DENGAN MENGGUNAKAN PERANGKAT LUNAK “R” UNTUK MENINGKATKAN KETERAMPILAN PENGOLAHAN DATA BAGI GURU - Puspa, Sofia Debi; Joko Riyono; Fani Puspitasari; Christina Eni Pujiastuti (Universitas Trisakti, 2024)
Regression analysis is a statistical method that aims to determine the relationship between one or more independent variables and the dependent variable. Correlation expresses the degree of linear relationship between the two variables. The application of regression and correlation analysis is needed, especially for teachers, to determine what factors influence students' understanding of learning and it can be seen how strongly a variable influences other variables. This Community Service Activity is motivated by the need for educators to analyze the causes of factors that influence students's understanding of learning through data. This Community Service for partners aims to provide understanding related to Correlation and regression Analysis with